A classification of “public and private” technologies in agriculture: an introductory framework - Penna, Julio A.; Lema, Rolando Daniel (IAMA (Estados Unidos), 2021)
Publicado como: Serie: Documentos de trabajo del Instituto de Economía y Sociología Nº 14. INTA. Ciudad Autónoma de Buenos Aires: Ediciones INTA. ISSN 1514-0555.